Case Report: Early Recognition, Treatment, and Occupational Safety Protection are Crucial for Methanol Toxicity - Wu, Xiaomei; Gu, Meifeng; Wang, Wei; Zhang, Hainan; Tang, Zhenchu (Frontiers in Medicine, 2022)
Background Despite significant progress in treating methanol poisoning, the lack of training, hazard communication, and occupational safety protection education contributes to the risk of occupational exposure and methanol toxicity. In addition, early diagnosis and timely medical care are essential to reduce the risk of morbidity and mortality, yet it remains a challenging procedure. Case report A 34-year-old man working in a fireworks factory came to our emergency department with acute mental change and progressive disturbance of consciousness. The patient’s vital signs were stable, and he presented with enlargement of both pupils with a weak reaction to light. Head computed tomography showed low signal intensities in the bilateral basal ganglia. He was admitted to the neurologic intensive care unit, where additional laboratory workup showed high anion-gap metabolic acidosis. Methanol poisoning was thus considered. Before being treated with sodium bicarbonate infusion, hemodialysis, folate, and high-dose vitamin B, the blood and urine samples were collected for toxicity tests, which turned out to be methanol poisoning. After 8 hours of hemodialysis, the patient consciousness recovered, but he complained of a complete loss of vision in both eyes. Brain and optic nerve magnetic resonance images showed bilateral symmetric putamen lesions and optic neuropathy. Ophthalmic tests indicated visual pathway impairment and optic disc swelling but no fluorescein leakage. The right eye's vision was partially restored on the third day, but he could only count fingers at 20cm. Unfortunately, his eyesight ceased to improve during the six months of follow-up. Conclusions Early diagnosis and prompt treatment will improve the prognosis of methanol poisoning in terms of vision and patient survival. Awareness and supervision of commercial alcohol use are indispensable for similar industrial processes.